“producción comparativa de cuatro densidades de siembras en el cultivo de frijol (phaseolus vulgaris), variedad huasca poroto huallaguino, empleando el sistema espaldera en la provincia de Lamas” - Ruíz Panduro, Elania Tejita (2015)
This research aimed to evaluate four stocking densities and determine the densities tend to increase grain yield in the cultivation of climbing beans (Phaseolus vulgaris L.) variety Huasca Poroto The Huallaga under the trellis system in the town of Lamas and perform economic analysis of the treatments studied. The research was conducted on the grounds of the Fundo "The Pacific" owned by Mr. Jorge Luis Pelaez Rivera, politically located in the district and province of Lamas, San Martin department. The statistical design of randomized complete block (DBCA) with three replications and five treatments, with a total of 15 experimental units was used. The information gathered in the field was processed using SPSS 19 statistical software, which uses the P-value as meaningful comparison to the confidence levels of 0.05 and 0.01 differences in the analysis of variance (ANOVA) and multiple range test of Duncan P :s; 0.05. The treatments were: TO: Witness (0.30 x 1.0 m), T1 (0.60 x 1.0 m), T2 (0.90 x 1.0 m), T3 (1.20 x 1.0 m), T4 (1.50 x 1.0 m). The variables evaluated were: emergency percentage, plant height (cm), number of pods per plant, number of seeds per pod, seed weight (g), yield (kg ha-1 ) and economic analysis. Planting was dated 18/08/14, and was conducted using a tacarpo and sinking to a depth of 5 cm, when the bean variety Huasca Poroto The Huallaga reached physiological maturity; that is, when 90% of pods changed color, and leaves tumed yellow by old age or most fell. The results obtained indicate that plants treated with the density of 6666.6, using a distance of 1.5 mx 1.0 m., Dueto soil and climatic conditions, proved to be the most appropriate treatment, determined to influence a higher yield of grain crops climbing bean (Phaseolus vu/garis L.) variety Huasca Poroto The Huallaga getting 5332.60 kg ha-1 , resulting in a benefit I cost ratio of 2.22 and a net profit of S l. 20,564.97, New Soles, respectively. Keywords: Culture, beans, comparativa densities, planting, evaluate, determine, performance, net profit.